Genome-wide CRISPR screening identifies LRP1 as an entry factor for SFTSV - Chen Xing; Cong Zhang; Zhihao Xu; Yajie Wang; Wanqing Lu; Xiaohan Liu; Yingying Zhang; Jingyuan Ma; Shuqi Yang; Yinan Du; Gang Xu; Yan Liu (Nature Communications)
Abstract Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne disease caused by the SFTS virus (SFTSV), which has high mortality rates and poses a significant threat to public health. To identify potential therapeutic targets against SFTSV, we conduct genome-wide knockout screening, which identifies the previously known host factor CCR2, and reveals prolow-density lipoprotein receptor-related protein 1 (LRP1) as an entry factor for SFTSV. Knockdown or knockout of LRP1 significantly attenuate SFTSV infection in mouse embryonic fibroblasts (MEFs). Additionally, inhibition of LRP1 suppresses SFTSV pseudovirus infection in MEFs, suggesting its role in viral entry. The interaction between the SFTSV glycoprotein Gn and LRP1 via the CLI and CLII domains is revealed by co-IP and surface plasmon resonance (SPR). Moreover, LRP1 antagonists and neutralizing antibodies effectively attenuate SFTSV infection in MEFs. Administration of an LRP1-neutralizing antibody in a lethal male mouse model reduces the viral load, mitigates tissue damage, and improves survival. This study identifies LRP1 as a host entry receptor for SFTSV, providing a target for therapeutic strategy development.